Social Union, Convergence and Migration - Hans-Werner Sinn; Wolfgang Ochel (Center for Economic Studies and ifo Institute (CESifo), 2003)
The forces of the market and systems competition bring about economic and social convergence in Europe. There is no need for social policies at the EU level. Social harmonisation would distort migration flows and slow down the speed of economic convergence. National welfare states will be threatened by the free migration of people in Europe. The race to the bottom is a serious risk. However, to contain this risk, neither harmonisation of welfare payments nor constraints on migration are needed. The adoption of the principle of selectively delayed integration is the better alternative.
Keywords: 330